Documents and Correspondence on New Guinea’s Boundaries
X, 212 p. 1 illus.
Keywords: This series of documents is a companion volume to Search for New Guinea's Boundaries: From Torres Strait to the Pacific (Australian National University Press, 1966). It brings together not only scattered, previously published documents, but also some of the correspondence surrounding them and reports and memoranda dealing with the bounda ries in general. The latter include material up to 1962. The documents have been arranged chronologically within sections. Material in sections A, B, and C corresponds respectively with matters dealt with in Chapters 2 (New Guinea Annexations), 3 (Papua Irredenta), and 4 (The Former Anglo-German Boundary), that in sections D, E, and F with those in Chapter 5 (The Irian Boundary), while that in section G is touched upon in the concluding chapter. The selection of published documents was simple: all were in eluded. Choice of unpublished material available in the archives was an individual one. Documents in Dutch, French, and German have been translated. Personal comments and queries have been entered in foot notes to the English translations which in all cases precede the original text. Cross references to Search for New Guinea's Boundaries, using the abbreviation S. N . G. B ., are made for the convenience of the reader.